Fatwa and Transnational Solidarity: Examining Faith-Based Movement in Indonesia in Addressing the Israel-Palestine Conflict - Noormansyah, Reza; Akhni, Ghaziah Nurika; Widyantoro, Sigid; Andini, Amalia Nur; Adinda, Seikha Citra; Amalia, Dinda Zafira (Perhimpunan Intelektual Muslim Indonesia, 2025)
This research explores the dynamics of transnational solidarity among Indonesian Muslims in their support of the Palestine cause, grounded in Fatwa MUI 83/2023, through the lens of Critical Discourse Analysis (CDA). This study investigates how religious and moral directives shape individual and collective actions. Data from questionnaires show that respondents' motivations to support Palestine stem from both humanitarian and religious convictions, amplified by the fatwa's ideological framework. The study finds that religious discourse transforms solidarity into concrete actions such as donations, boycotts, and digital activism. Furthermore, the fatwa facilitates the globalization of local actions, linking grassroots efforts to a broader international campaign for Palestinian rights. This research underscores the power of religious authority in shaping transnational solidarity movements and highlights how digital platforms enable local actions to resonate globally.